NCERT Solutions for Class 11 Maths Chapter 8 Binomial Theorem: Overview, Questions, Preparation

NCERT Maths 11th 2023 ( Maths Ncert Solutions class 11th )

Salviya Antony
Updated on Dec 19, 2024 14:48 IST

By Salviya Antony, Senior Executive - Content

Binomial Theorem Class 11 NCERT Solutions: We provide NCERT Solutions Maths Class 11 Chapter 7 Binomial Theorem on this page. Students are advised to go through the Class 11 Maths Chapter 7 Binomial Theorem solutions so that they will get a clear idea of the concepts. These solutions are developed by our subject experts. Students can refer to this page and find the solutions of all the questions in the exercises of this chapter. Students can download NCERT Solutions Maths Chapter 7 Binomial Theorem Class 11 PDF from this page. They are advised to solve Binomial theorem class 11 NCERT solutions. They can access NCERT Solutions for free.

The expansion of a binomial for any positive integral n is given by Binomial Theorem. This theorem is used as an easier way to expand (a + b)n , where n is an integer or a rational number. Practicing the solutions of Binomial theorem will definitely help students to improve their speed of solving problems. These are beneficial for those who are preparing for board exams as well as entrance exams.

Binomial Theorem Class 11 - Topics Covered

  • Binomial Theorem for Positive Integral Indices
  • Pascal’s Triangle

Check the NCERT Solutions Maths Class 11 Chapter 7 Binomial Theorem below.

Q8.1 (1-2x)5

A 8.1 (1-2x)5

By using binomial theorem we have,
= 5C0 (1)5+ 5C1(1)4 (-2x) + 5C2 (1)3 (-2x)2+5C3 (1)2(-2x)3+ 5C4 (1)1(-2x)4+5C5 (-2x)5
= [5! / 0! (5-0!) X 1] + [5! / 1! 5-1! X 1 X ( -2x )] +[x1× (4x2)] + [5! / 3! 5-3! X 1 X ( -8x3 )] +[5! / 4! 5-4! X 1 X (16x4 )] + [5! / 5! 5-5! X 1 X ( 32x5 )]
= 1 + [5 X 4! / 1X 4! X -2x] + [5X4X3! / 2X1X3! X4x2] + [5X4X3! / 3!X2!-(-8x3)] + [5X4! / 4! X1X16x4]+ [1X(-32x5)]
= 1 + [5 × (–2x)] + [10 × 4x2] + [10 × (–8x3)] + [5 × 16x4] + [–32x5]
= 1 – 10x + 40x2 – 80x3 + 80x4 – 32x5

Download Here NCERT Class 11th Maths Chapter 7 Binomial Theorem Solutions and PDF

Table of content
  • Binomial Theorem Class 11 Solutions and FAQs
Maths Ncert Solutions class 11th Logo

Binomial Theorem Class 11 Solutions and FAQs

Exercise 8.1

Expand each of the expressions in Exercises 1 to 5.

Q1. (1–2x)5

A.1. (1 – 2x)5

By using binomial theorem we have,

= 5C0 (1)5+5C1 (1)4 (-2x) + 5C2 (1)3 (-2x)2+5C3 (1)2 (-2x)3+5C4 (1)1 (-2x)4+5C5 (-2x)5

( 5 ! 0 ! ( 5 0 ) !
′ 1
)
+ [ 5 ! 1 ! ( 5 1 ) ! 1 ( 2 x ) ] +[x1× (4x2)] +  [ 5 ! 3 ! ( 5 3 ) ! 1 ( 8 x 3 ) ]  +  [ 5 ! 4 ! ( 5 4 ) ! 1 ( 1 6 x 4 ) ]  +  [ 5 ! 5 ! ( 5 5 ) ! ( 3 2 x 5 ) ]

= 1 +  [ 5′
4 !
1′  
4 !
( 2 x )
]
 +  [ 5′
4′
3 !
2′
1′
3 !
× 4 x 2
]
 +  [ 5′
4′
3 !
3 !′
2 !
× ( 8 x 3 )
]
 +  [ 5′
4 !
4 !′  
1
× 1 6 x 4
]
+ [1 × (-32x5)]

= 1 + [5 × (–2x)] + [10 × 4x2] + [10 × (–8x3)] + [5 × 16x4] + [–32x5]

= 1 – 10x + 40x2 – 80x3 + 80x4 – 32x5

 

Q2. ( 2 x x 2 ) 5

A.2. ( 2 x x 2 ) 5

Using (xy)n

=  5C0 ( 2 x ) 5 5C1 ( 2 x ) 4   ( x 2 ) + 5C2 ( 2 x ) 3   ( x 2 ) 2 5C3 ( 2 x ) 2   ( x 2 ) 3 + 5C4 ( 2 x )   ( x 2 ) 4 5C5 ( x 2 ) 5

[ 5 ! 0 ! ( 5 0 ) !
′3 2 x 5
]
 –  [ 5 ! 1 ! ( 5 1 ) ! 1 6 x 4 × x 2 ]  +  [ 5 ! 2 ! ( 5 2 ) ! 8 x 3 x 2 4 ]  –  [ 5 ! 3 ! ( 5 3 ) ! 4 x 2 x 3 8 ]  +  [ 5 ! 4 ! ( 5 4 ) ! x 2 x 4 1 6 ]  –  [ 5 ! 5 ! ( 5 5 ) ! x 5 3 2 ]

[ 1 3 2 x 5 ]  –  [ 5 4 ! 1 4 ! 8 x 3 ]  +  [ 5 4′
3 !
2
1′
3 !
2 x
]
 –  [ 5′
4′
3 !
3 !′  
2 !
× x 2
]
 +  [ 5′  
4 !
4 !′  
1 !
x 3 8
]
 –  [ 1′
x 5 3 2
]

3 2 x 5  –  4 0 x 3  +  2 0 x  – 5x +  5 8 x 3  –  x 5 3 2

 

Q3. (2x – 3)6

A.3. (2x – 3)6

By using binomial theorem,

(2x – 3)6

= 6C0 (2x)6  +  6C1 (2x)5(–3)  +  6C2 (2x)4(–3)2  +  6C3 (2x)3(–3)3  +  6C4 (2x)2(–3)4  +  6C5 (2x)(–3)56C6 (–3)6

 

= 64x6  –  576x5  +  2160x4  –  4320x3  +  4860x2  –  2916x  +  729

 

Q4. ( x 3 + 1 x ) 5

A.4. ( x 3 + 1 x ) 5

By using binomial theorem,

 

x 5 2 4 3  +  5 x 3 8 1  +  1 0 x 2 7  +  1 0 9 x  +  5 3 x 3  +  1 x 5

 

Q5. ( x + 1 x ) 6

A.5. ( x + 1 x ) 6

By binomial theorem,

 

x 6  + 6  x 4  + 15  x 2  + 20 +  1 5 x 2  +  6 x 4  +  1 x 6

Using binomial theorem, evaluate each of the following:

 

Q6. (96)3

A.6. (96)3 = (100 – 4)3

Using (xy)n expansion

= 3C0(100)33C1(100)2(4) + 3C2(100)(4)23C3(4)3

 

= 1000000 – 120000 + 4800 – 64

= 1004800 – 120064

= 884736

 

Q7. (102)5

A.7. (102)5 = (100 + 2)5

By using binomial theorem,

= 5C0(100)5 + 5C1(100)4(2) + 5C2(100)3(2)2 + 5C3(100)2(2)3 + 5C4(100)(2)4 + 5C5(2)5

[ 5 ! 0 ! ( 5 0 ) ! 1 0 0 0 0 0 0 0 0 0 0 ]  +  [ 5 ! 1 ! ( 5 1 ) ! 0 0 0 0 0 0 0 0 2 ]  +  [ 5 ! 2 ! ( 5 2 ) ! 1 0 0 0 0 0 0 4 ]  +  [ 5 ! 3 ! ( 5 3 ) ! 1 0 0 0 0 8 ]  +  [ 5 ! 4 ! ( 5 4 ) ! 1 0 0 1 6 ]  +  [ 5 ! 5 ! ( 5 5 ) ! 3 2 ]

= [1 × 10000000000] +  [ 5′
4 !
1′
4 !
0 0 0 0 0 0 0 0
]
 +  [ 5′
4′
3 !
2′
1′
3 !
4 0 0 0 0 0 0
]
 +  [ 5′
4′
3 !
3 !′  
2 !
8 0 0 0 0
]
 +  [ 5′
4 !
4 !′  
1 !
1 6 0 0
]
 + [1 × 32]

= 10000000000 + 1000000000 + 40000000 + 800000 + 8000 + 32

= 11040808032

 

Q8. (101)4

A.8. (101)4 = (100 + 1)4

By binomial theorem we get,

= 4C0(100)4 + 4C1(100)3(1) + 4C2(100)2(1)2 + 4C3(100)(1)3 + 4C4(1)4

[ 4 ! 0 ! ( 4 0 ) ! 0 0 0 0 0 0 0 0 ]  +  [ 4 ! 1 ! ( 4 1 ) ! 0 0 0 0 0 0 1 ]  +  [ 4 ! 2 ! ( 4 2 ) ! 1 0 0 0 0 1 ]  +  [ 4 ! 3 ! ( 4 3 ) ! 1 0 0 1 ]  +  [ 4 ! 4 ! ( 4 4 ) ! 1 ]

= [1 × 100000000] +  [ 4′
3 !
1′
3 !
1 0 0 0 0 0 0
]
 +  [ 4′
3′
2 !
2′
1′
2 !
1 0 0 0 0
]
 +  [ 4′
3 !
3 !′  
1 !
1 0 0
]
 +[1 × 1]

= 100000000 + 4000000 + 60000 + 400 + 1

= 104060401

 

Q9. (99)5

A.9. (99)5 = (100 – 1)5

By binomial theorem we get,

= 5C0(100)55C1(100)4(1) + 5C2(100)3(1)25C3(100)2(1)3 + 5C4(100)(1)45C5(1)5

[ 5 ! 0 ! ( 5 0 ) ! 1 0 0 0 0 0 0 0 0 0 0 ]  –  [ 5 ! 1 ! ( 5 1 ) ! 0 0 0 0 0 0 0 0 1 ]  +  [ 5 ! 2 ! ( 5 2 ) ! 0 0 0 0 0 0 1 ]  –  [ 5 ! 3 ! ( 5 3 ) ! 1 0 0 0 0 1 ]  +  [ 5 ! 4 ! ( 5 4 ) ! 1 0 0 1 ]  –  [ 5 ! 5 ! ( 5 5 ) ! 1 ]

= [1 × 10000000000] –  5′
4 !
1′
4 !
0 0 0 0 0 0 0 0
 +  [ 5′
4′
3 !
2′
1′
3 !
1 0 0 0 0 0
]
 –  [ 5′
4′
3 !
3 !′  
2 !
1 0 0 0 0
]
 +  [ 5′
4 !
4 !′  
1 !
1 0 0
]
 – [1 × 1]

= 10000000000 – 500000000 + 10000000 – 100000 + 500 – 1

= 10010000500 – 500100001

= 9509900499

 

Q10. Using Binomial Theorem, indicate which number is larger (1.1)10000or 1000.

A.10. We know that,

(1.1)10000 = (1 + 0.1)10000

By using binomial theorem,

= 10000C0(1)10000 + 10000C1 (1)(10000 – 1) (0.1) + other positive terms

[ 1 0 0 0 0 ! 0 ! ( 1 0 0 0 0 0 ) ! 1 ]  +  [ 1 0 0 0 0 ! 1 ! ( 1 0 0 0 0 1 ) ! 1 0 . 1 ]  + other positive terms

= [1 × 1] +  [ 1 0 0 0 0′  
9 9 9 9 !
1′
9 9 9 9 !
0 . 1
]
 + other positive terms

= 1 + 1000 + other positive terms

= 1001 + other positive terms

Hence, (1.1)10000> 1000

 

Q11. Find (a + b)4– (a – b)4. Hence, evaluate (√3 +√2 ) 4 (√3 −√2 ) 4 .

A.11. Using binomial theorem we have,

(a + b)4 – (ab)4

= [4C0a4 + 4C1a3b + 4C2a2b2 + 4C3ab3 + 4C4b4] – [4C0a44C1a3b + 4C2a2b24C3ab3 + 4C4b4]

= 4C0a4 + 4C1a3b + 4C2a2b2 + 4C3ab3 + 4C4b44C0a4 + 4C1a3b4C2a2b2 + 4C3ab34C4b4

= [2 ×4C1a3b] + [2 ×4C3ab3]

[ 2′
4 ! 1 ! ( 4 1 ) ! a 3 b
]
 +  [ 2′
4 ! 3 ! ( 4 3 ) ! a b 3
]

[ 2′
4′
3 !
1′
3 !
a 3 b
]
 +  [ 2′
4′
3 !
3 !
1 !
a b 3
]

= 8a3b + 8ab3

Hence putting a = √3 and b = √2  we have,

(√3 +√2 ) 4  –  (√3 −√2 ) 4

= 8  (√3 ) 3 (√2 )  + 8  (√3 )   (√2 ) 3

= (8 × 3 √3 ×√2  )+ (8 × √3 × 2 √2  )

= 24 √6 + 16 √6

= 40 √6

Q12. Find (x + 1)6+ (x – 1)6. Hence or otherwise evaluate (√2 + 1 ) 6 + (√2 1 ) 6 .

A.12. By binomial expansion we have,

( x + 1 ) 6  +  ( x 1 ) 6

= [6C0(x6) + 6C1(x5)(1) + 6C2(x4)(1) 2 + 6C3(x3)(1)3 + 6C4(x2)(1)4 + 6C5(x)(1)5 + 6C6(1)6] + [6C0(x6) – 6C1(x5)(1) + 6C2(x4)(1) 26C3(x3)(1)3 + 6C4(x2)(1)46C5(x)(1)5 + 6C6(1)6]

= 6C0(x6) + 6C1(x5)(1) + 6C2(x4)(1) 2 + 6C3(x3)(1)3 + 6C4(x2)(1)4 + 6C5(x)(1)5 + 6C6(1)6 + 6C0(x6) – 6C1(x5)(1) + 6C2(x4)(1) 26C3(x3)(1)3 + 6C4(x2)(1)46C5(x)(1)5 + 6C6(1)6

= 2 × [6C0(x6) + 6C2(x4)(1) 2 + 6C4(x2)(1)4 + 6C6(1)6]

= 2 ×  [ ( 6 ! 0 ! ( 6 0 ) ! x 6 ) + ( 6 ! 2 ! ( 6 2 ) ! 6 ! 2 ! ( 6 2 ) ! + x 4 1 )  +  ( 6 ! 4 ! ( 6 4 ) ! x 2 1 ) + ( 6 ! 6 ! ( 6 6 ) ! 1 ) ]

= 2 × [(1 ×  x 6  ) +  ( 6′
5′
4 !
2′  
1′
4 !
x 4
)
+ ( 6′
5′
4 !
4 !′  
2 !
x 2
)
 + (1 × 1)]

= 2[  x 6  + 15  x 4  + 15  x 2  + 1]

Hence putting x = √2  we have,

( √2 + 1)6 + ( √2 – 1)6

= 2 × [  (√2 ) 6  + 15  (√2 ) 4  + 15  (√2 ) 2  + 1]

= 2 × [23 + (15 x 22) + (15 x 2) + 1]

= 2 × [8 + 60 + 30 + 1]

= 2 × 99

= 198

 

Q13. Show that 9n+1– 8n – 9 is divisible by 64, whenever n is a positive integer.

A.13. For a number x to be divisible by y, we can write x as a factor of y i.e., x = ky where k is some natural number. Thus in order for 9n+1 – 8n – 9 to be divisible by 64 we need to show that 9n+1 – 8n – 9 = 64k where k is some natural number.

We have, by binomial theorem

(1 + a)m = mC0 + mC1(a) + mC2(a)2 + mC3(a)3 + ………… + mCm(a)m

Putting, a = 8 and m = n + 1

(1 + 8)n+1 = n+1C0 + n+1C1.8 + n+1C2.82 + n+1C3.83 + …….. + n+1Cn+1.(8)n+1

=> 9n+1=  1 + (n + 1)8 + 82×[n+1C2 + n+1C3.8 + ……….. + n+1Cn+1.(8)n+1–2]  [since, n+1C0 = 1, n+1C1= n + 1]

=> 9n+1 = 1 + 8n + 8 + 64 × [n+1C2 + n+1C3.8 + ……….. + n+1Cn+1.(8)n+1-2]

=> 9n+1 – 8n – 9 = 64 × [n+1C2 + n+1C3.8 + ……….. + 8n–1][since, n+1Cn+1 = 1]

=> 9n+1 – 8n – 9 = 64k,

where k = n+1C2 + n+1C3.8 + ……….. + 8n–1 is a natural number.

This shows that 9n+1 – 8n – 9 is divisible by 64

 

Q14. Prove that r = 0 n 3 r n C r = 4 n .

A.14.

By binomial theorem,

(a + b)n = nC0(a)n(b)0 + nC1(a)n–1(b)1 + ………….. + nCr(a)nr(b)r + …………… + nCn(a)nn(b)n

Where, b0 = 1 = ann

So, (a + b)n = nCr(a)nr(b)r

Putting a = 1 and b = 3 such that a + b = 4 , we can rewrite the above equation as

(1 + 3)n = nCr(1)nr.3r

=>4n = r = 0 . 3 r .nCr

Hence proved.

 

Exercise 8.2

Find the coefficient of

Q1. x5in (x + 3)8

A.1. Let x5 occurs in (r + 1)th term of the expansion (x + 3)8.

Now, Tr+1 = 8Cr . x 8 r . 3 r

Comparing indices of x in Tr+1 with x5 we get,

8 – r = 5

=>r = 8 – 5 = 3

So, Co-efficient of x5 is

8C3× 33

8 ! 3 ! ( 8 3 ) !  × 27

8′
7′
6′
5 !
3′
2′
1′
5 !
 × 27

= 56 × 27

= 1512

 

Q2. a5b7in (a – 2b)12.

A.2. Let a5b7 occurs in (r + 1)th term of [removed]a – 2b)12.

Now, Tr+1 = 12Cra12-r (–2b)r

= (–1)r12Cra12–r . 2r. br

Comparing indices of a and b in Tr-1 with a5 and b7 we get,

r = 7

So, co-efficient of a5b7 is (–1)712C7 27

= –1 ×  1 2 ! 7 !′  
( 1 2 7 ) !
× 27

= –1 ×  1 2′
1 1′
1 0′
9′
8′
7 !
7 !′  
5 !
 × 128

= –1 ×  1 2′
1 1′
1 0′
9′
8
5′
4′
3′
2′
1
 × 128

= –1 × 792 × 128

= – 101376

Write the general term in the expansion of

 

Q3. (x2y)6

A.3. Let (r + 1)th term be the general term of (x2y)6.

So, Tr-1 = 6Cr (x2)6-r (-y)r

= (–1)r .6Cr . x 1 2 r  .  y r

 

Q4.(  x 2   y x ) 1 2  , x≠ 0.

A.4. Let (r + 1)th be the general term of ( x 2   y x ) 1 2

So, Tr-1 = 12Cr (x2)12–r (–yx)r

= (–1)r12Crx24–2ryrxr

= (–1)r12Cr x 2 4 2 r + r y r

= (-1)r12C­r x 2 4 r y r

 

Q5. Find the 4thterm in the expansion of (x – 2y)12.

A.5. General term of the expansion ( x 2 y ) 1 2  is given by

Tr+1 = 12Cr ( x ) 1 2 r ( 2 y ) r

For 4th term, r + 1 = 4 i.e., r = 3

Therefore, T4 = T3+1 = 12C3 ( x ) 1 2 3 ( 2 y ) 3

1 2 ! 3 ! ( 1 2 3 ) !   x 9 ( 1 ) 3 2 3 y 3

1 2′
1 1′
1 0′
9 !
3′
2′
1′
9 !
  ( x ) 9  × (8  y ) 3

= – 220 x9× 8y3

= – 1760x9y3

 

Find the middle terms in the expansions of

 

Q7.  ( 3 x 3 6 ) 7

A.7. As n = 7 is odd, the middle term are the ( n + 1 2 ) t h  term and  ( n + 1 2 +   1 ) t h  term. i.e.  ( 7 + 1 2 ) t h  and  ( 7 + 1 2 + 1 ) t h term which is 4th term and 5th term. i.e. T4 and T5.

Hence, T4 = T3+1 = 7C3(3)7-3 ( x 3 6 ) 3

7 ! 3 ! ( 7 3 ) ! × 34 (–1)3 ( x 3 2 3 . 3 3 )

7′
6′
5′
4 !
3′
2′
1′
4 !
 ×  3 4 3 3  ×  x 9 2 3

= – 35 ×  3 x 9 8

1 0 5 x 9 8

T5 = T4+1 = 7C4× (3)7-4 ( x 3 6 ) 4

7 ! 4 ! ( 7 4 ) !  ×  3 3 x 1 2 2 4 3 4

7′
6′
5′
4 !
4 !   3 !
 ×  x 1 2 2 4 3

7′
6′
5
3′
2′
1
 ×  x 1 2 1 6′  
3

3 5 x 1 2 4 8

 

Q8.  ( x 3 + 9 y ) 1 0 .

A.8. As n = 10 is even the middle term is ( n 2 + 1 ) t h  i.e.  ( 1 0 2 + 1 ) t h  term i.e. 6th term.

So, T6 = T5+1 = 10C5 ( x 3 ) 1 0 5 (9y)5

1 0 ! 5 ! ( 1 0 5 ) !  ×  x 5 3 5 × 35x2y5

1 0′
9′
8′
7′
6′
5 !
5′
4′
3′
2′
1′
5 !
× 35x5y5

= 2 × 9 × 2 × 7 × 243 x5y5

= 61236 x5y5

 

Q9. In the expansion of (1 + a)m+n,prove that coefficients of anand anare equal.

A.9. The general term of the expansion (1 + a)m+n is

Tr+1 = m+nCrar   [since, 1m+n-r = 1]

At r = m we have,

Tm+1 = m+nCmam

( m + n ) ! m ! ( m + n m ) ! (a)m

( m + n ) ! m !   n ! am --------------- (1)

Similarly at r = n we have,

Tn+1 = m+nCnan

( m + n ) ! n ! ( m + n n ) ! (a)n

( m + n ) ! n !   m ! an --------------- (2)

Hence from (1) & (2),

Co-efficient of am = Co-efficient of an = ( m + n ) ! m ! n !

 

Q10. The coefficients of the (r – 1)th, rthand (r + 1)thterms in the expansion of (x + 1)n are in the ratio 1 : 3 : 5. Find n and r.

A.10. The general term of the expansion (x +1)n is

Tr+1 = nCrxnr1r

i.e. co-efficient of  ( r + 1 ) t h term = nCr

So, co-efficient of  ( r 1 ) t h term =nC(r–1) – 1 = nCr – 2

Similarly, co-efficient of rth term = nCr – 1

Given that, nCr – 2 :nCr – 1 : nCr = 1 : 3 : 5

We have,

 

 

 =  1 3

=>  n ! ( r 2 ) ! ( n r + 2 ) !  ×  ( r 1 ) ! ( n r + 1 ) ! n !  =  1 3

=>  ( r 1 ) ( r 2 ) ! ( n r + 1 ) ! ( r 2 ) ! ( n r + 2 ) ( n r + 1 ) !  =  1 3

=>  ( r 1 ) ( n r + 2 )  =  1 3

=> 3r – 3 = n – r + 2

=> 3r + r = n + 2 + 3

=> 4r = n + 5 -------------- (1)

And,

 

 =  3 5

=>  n ! ( r 1 ) ! ( n r + 1 ) !  ×  r ! ( n r ) ! n !  =  3 5

=>  r ( r 1 ) ! ( n r ) ! ( r 1 ) ! ( n r + 1 ) ( n r ) !  =  3 5

=>  r n r + 1  =  3 5

=> 5r = 3n – 3r + 3

=> 5r + 3r = 3n + 3

=> 8r = 3n + 3 ----------------------- (2)

Multiplying equation (1) by 2 and subtracting from equation (2) we get,

8r – 8r = 3n + 3 – (2n + 10)

=> 0 = 3n + 3 – 2n – 10

=> 0 = n – 7

=>n = 7

Putting n = 7 in equation (1) we get,

=> 4r = 7 + 5

=>r =  1 2 4

=>r = 3

 

Q11. Prove that the coefficient of xnin the expansion of (1 + x)2nis twice the coefficientof xnin the expansion of (1 + x)2n-1.

A.11. General term of the expansion (1 + x)2n is

Tr+1 = 2nCr (1)2n-r(x)r

So, co-efficient of xn (i.e. r = n) is 2nCn

Similarly general term of the expansion (1 + x)2n–1 is

Tr+1 = 2n-1Cr (1)2n–1–rxr

And co-efficient of xn i.e. when r = n is 2n-1Cn

Therefore,

c o e f f i c i e n t   o f   x n   i n   ( 1 + x ) 2 n c o e f f i c i e n t   o f   x n   i n   ( 1 + x ) 2 n 1

=

2 n ! n ! ( 2 n n ) !  ÷  ( 2 n 1 ) ! n ! ( 2 n 1 n ) !

2 n ! n ! n !  ×  n ! ( n 1 ) ! ( 2 n 1 ) !

2 n′  
( 2 1 ) !
n !′  
n′
( n 1 ) !
 ×  n ! ( n 1 ) ! ( 2 n 1 ) !

2 n n

= 2

Thus, co-efficient of  x n  in  ( 1 + x ) 2 n  = 2x co-efficient of  x n  in  ( 1 + x ) 2 n 1

 

Q.12. Find a positive value of m for which the coefficient of x2in the expansion (1 + x)m is 6.

A.12. The general term of the expansion  ( 1 + x ) m  is given by,

Tr+1 = mCr 1 m r   x r

= mCrxr

At r = 2,

T2+1 = mC2x2

Given that, co-efficient of x2 = 6

=>mC2 = 6

=>  m ! 2 ! ( m 2 ) !  = 6

=>  m′  
( m 1 )′
( m 2 ) !
2′  
1′
( m 2 ) !
 = 6

=>  m′  
( m 1 )
2
 = 6

=>m2 – m = 12

=>m2 – m – 12 = 0

=>m2 + 3m – 4m – 12 = 0

=>m(m + 3) – 4(m+ 3) = 0

=> (m – 4)(m + 3) = 0

=>m = 4 and m = –3

Since, we need a positive value of m we have,

m = 4

 

Miscellaneous Exercise

Q1. Find a, b and n in the expansion of (a + b)n if the first three terms of the expansion are 729, 7290 and 30375, respectively.

A.1.The general term of the expansion (a + b)n is given by

Tr +1 = nCranrbr

So, T1 = nC0an = an

T2 = nC1an-1b = n ! 1 ! ( n 1 ) ! an-1 b = n × ( n 1 ) ! ( n 1 ) ! an-1b = nan-1b

T3 = nC2an-2b2 = n ! 2 ! ( n 2 ) [ ! an-2b2 = n   × ( n 1 ) × ( n 2 ) ! 2 × 1 × ( n 2 ) ! an-2b2 = n ( n 1 ) 2 an-2b2

Given,

T1 = 729

=>an = 729 ------------------ (1)

T2 = 7290

=>nan–1b = 7290 ------------- (2)

T3 = 30375

=>  n ( n 1 ) 2 an–2b2 = 30375 ------------------- (3)

Dividing equation (2) by (1) we get,

n a n 1 b a n  =  7 2 9 0 7 2 9

=>  n b a  = 10

Similarly dividing equation (3) by (2) we get,

n ( n 1 ) 2 an–2b2 ÷ nan–1b = 3 0 3 7 5 7 2 9 0

=>  n ( n 1 ) 2 an–2b2×  1 n a n 1 b  =  3 0 3 7 5 7 2 9 0

=>  n ( n 1 ) a n 2 b 2  ×  1 n a n 1 b  =  3 0 3 7 5 7 2 9 0  × 2

=>  ( n 1 ) b a  =  2 5′   × 2 6

=>  n b a   b a  =  2 5 3

=> 10 –  b a  =  2 5 3  [since,  n b a  = 10]

=>  b a  = 10 –  2 5 3

3 0 2 5 3

5 3  --------------- (5)

Putting equation (5) in (4) we get,

n×  5 3  = 10

=>n = 10 ×  3 5

=>n = 6

So putting the value of n in equation (1) we get,

a6 = 729

=>a6= 36

=>a = 3

And putting a = 3 in equation (5) we get,

b a  =  5 3

=>b =  5 3  ×a

5 3  × 3

= 5

 

Q2. Find a if the coefficients of x2and x3in the expansion of (3 + ax)9are equal.

A.2. The general term of the expansion  ( 3 + a x ) 9  is

Tr+1 = 9Cr 3 ( 9 r )   ( a x ) r

= 9Cr 3 ( 9 r ) a r x r

At r = 2,

T2+1 = 9C2 3 ( 9 2 ) a 2 x 2

9 ! 2 ! ( 9 2 ) ! 37a2x2

9′
8′
7 !
2′
1′
7 !
37a2x2

= 36 ×37a2x2

At r = 3,

T3+1 = 9C3 3 ( 9 3 ) a 3 x 3

9 ! 3 ! ( 9 3 ) ! 36a3x3

9′
8′
7′
6 !
3′  
2′
1′
6 !
36a3x3

= 84 ×36a3x3

Given that,

Co-efficient of  x 2  = co-efficient of  x 3

=> 36 ×  3 7 a 2  = 84 ×  3 6 a 3

=>  a 3 a 2  =  3 6′
3 7
8 4′  
3 6

=>  a  =  3′
3
7

9 7

 

Q3. Find the coefficient of x5in the product (1 + 2x)6(1 – x)7using binomial theorem.

A.3. We first expand each of the factors of the given product using Binomial theorem. We have,

(1 + 2x)6= 6C0 (1)6  +  6C1 (1)5(2x)  +  6C2 (1)4(2x)2  +  6C3 (1)3(2x)3  +  6C4 (1)2(2x)4  +  6C5 (1)(2x)5  +  6C6(2x)6

[ 6 ! 0 ! ( 6 0 ) ! 1 ]  +  [ 6 ! 1 ! ( 6 1 ) ! 1 ( 2 x ) ]  +  [ 6 ! 2 ! ( 6 2 ) ! 1 4 x 2 ]  +  [ 6 ! 3 ! ( 6 3 ) ! 1 8 x 3 ]  +  [ 6 ! 4 ! ( 6 4 ) ! 1 1 6 x 4 ]  +  [ 6 ! 5 ! ( 6 5 ) ! 1 3 2 x 5 ]  +  [ 6 ! 6 ! ( 6 6 ) ! 6 4 x 6 ]

= [1] +  [ 6′  
5 !
1′  
5 !
( 2 x )
]
 +  [ 6′
5′
4 !
2′
1′
4 !
4 x 2
]
 +  [ 6′
5′
4′
3 !
3′  
2′
1′
3 !
( 8 x 3 )
]
 +  [ 6′
5′
4 !
4 !′  
2 !
1 6 x 4
]
 +  [ 6′
5 !
5 !′  
1 !
( 3 2 x 5 )
]
 + [1 ×64x6]

= 1 + 12  x + 60x2 + 160x3 + 240x4 + 192x5 + 64x6

And,

(1 – x)7= 7C0 (1)7  +  7C1 (1)6(–x) + 7C2 (1)5(–x)2 + 7C3 (1)4(–x)3  +  7C4 (1)3(–x)4  +  7C5 (1)2(–x)5  +  7C6 (1) (–x)6 + 7C7(–x)7

[ 7 ! 0 ! ( 7 0 ) ! 1 ]  +  [ 7 ! 1 ! ( 7 1 ) ! 1 ( x ) ]  +  [ 7 ! 2 ! ( 7 2 ) ! 1 x 2 ]  +  [ 7 ! 3 ! ( 7 3 ) ! 1 ( x ) ]  +  [ 7 ! 4 ! ( 7 4 ) ! 1 x 4 ]  +  [ 7 ! 5 ! ( 7 5 ) ! 1 ( x ) 5 ]  +  [ 7 ! 6 ! ( 7 6 ) ! 1 x 6 ]  + [  [ 7 ! 7 ! ( 7 7 ) ! ( x ) 7 ]

= [1] +  [ 7′  
6 !
1′  
6 !
( x )
]
 +  [ 7′  
6′
5 !
2′
1′
5 !
x 2
]
 +  [ 7′
6′
5′
4 !
3′  
2′
1′
4 !
( x 3 )
]
 +  [ 7′  
  6′
5′
4 !
4 !′  
3 !
x 4
]
 +  [ 7′
6′ 5 !
5 !′  
2 !
( x 5 )
]
 +  [ 7′
6 !
6 !′  
1 !
x 6
]
 + [1 ×(–x)7]

= 1 – 7x + 21x2 – 35x3 + 35x4– 21x5 + 7x6x7

Thus,  ( 1 + 2 x ) 6 ( 1 x ) 7

= (1 + 12x + 60x2 + 160x3 + 240x4 + 192x5 + 64x6)( 1 – 7x + 21x2 – 35x3 + 35x4– 21x5 + 7x6x7)

We need to find only the term involving x5 i.e. xrx5 – r

The terms with x5 are

= (1)(–21x5) + (12x)(35x4) + (60x2)(–35x3) + (160x3)(21x2) + (240x4)(–7x) + (192x5)(1)

= –21x5 + 420x5– 2100x5 + 3360x5– 1680x5 + 192x5

= 3972x5– 3801x5

= 171x5

Hence, co-efficient of x5 is 171.

 

Q4. If a and b are distinct integers, prove that a – b is a factor of anbn, whenever n is a positive integer.

[Hint: write an= (a b + b)n and expand]

A.4. For (a – b) to be a factor of anb nwe need to show (anbn) = (ab)k as k is a natural number.

We have, for positive n

an = ( a b + b ) n  =  [ ( a b ) + b ] n

=>an = nC0(ab)n + nC1(ab)n -1b + nC2(ab)n – 2b2 + ………… +nCn-1  ( a b )   b n 1 + nCnbn

=>an= ( a b ) n + nC1 ( a b ) n 1   b + nC2 ( a b ) n 2   b 2 + …………….…+ nCn-1 ( a b )   b n 1  +  b n [Since, nC0 = 1 and nCn = 1]

=>  a n b n  =  ( a b ) n +nC1  ( a b ) n 1   b + nC2 ( a b ) n 2   b 2 + ……………… + nCn-1 ( a b )   b n 1

=>  a n b n  =  ( a b )  [  ( a b ) n 1 + nC1 ( a b ) n 2   b + nC2 ( a b ) n 3   b 2 +………..…… + nCn-1   b n 1  ]

=>  a n b n  =  ( a b )  k where k = [  ( a b ) n 1 + nC1 ( a b ) n 2   b + nC2 ( a b ) n 3   b 2 +………..…… + nCn-1   b n 1  ] is a natural number.

Therefore (a – b) is a factor of anbnwhere n is positive integer.

 

 

Q7. Find an approximation of (0.99)5using the first three terms of its expansion.

A.7. (0.99)5 = (1 – 0.01)5

By binomial theorem expanding upto first three terms, we get

(1 – 0.01)5 = 5C0 (1)5 + 5C1 (1)4(-0.01) + 5C2 (1)3(-0.01)2

( 5 ! 0 ! ( 5 0 ) ! 1 )  +  [ 5 ! 1 ! ( 5 1 ) ! 1 ( 0 . 0 1 ) ]  +  ( 5 ! 2 ! ( 5 2 ) ! 1 0 . 0 0 0 1 )

= (1 × 1) –  ( 5′
4 !
1′
4 !
1 0 . 0 1
)
 +  ( 5′
4′
3 !
2′
1′
3 !
1 0 . 0 0 0 1
)

= 1 – 0.05 + 0.001

= 1.001 – 0.05

= 0.951

 

Q9. Expand using Binomial Theorem ( 1 + x 2 2 x ) 4 , x 0 .

A.9.  ( 1 +   x 2 2 x ) 4

Using binomial theorem we have,

[ ( 1 + x 2 ) 2 x ] 4

= 4C0 ( 1 + x 2 ) 4 + 4C1 ( 1 + x 2 ) 3 ( 2 x ) + 4C2 ( 1 + x 2 ) 2 ( 2 x ) 2 + 4C3 ( 1 + x 2 ) ( 2 x ) 3 + 4C4 ( 2 x ) 4

[ 4 ! 0 ! ( 4 0 ) ! ( 1 + x 2 ) 4 ]  –  [ 4 ! 1 ! ( 4 1 ) ! ( 1 + x 2 ) 3 ( 2 x ) ]  +  [ 4 ! 2 ! ( 4 2 ) ! ( 1 + x 2 ) 2 ( 4 x 2 ) ]  –  [ 4 ! 3 ! ( 4 3 ) ! ( 1 + x 2 ) ( 8 x 3 ) ]  +  [ 4 ! 4 ! ( 4 4 ) !   ( 1 6 x 4 ) ]

1′
( 1 + x 2 ) 4
 –  [ ( 1 + x 2 ) 3 ( 2 x ) ]  +  [ 4′
3′
2 !
2′
1′
2 !
( 1 + x 2 ) 2 ( 4 x 2 )
]
 –  [ 4 3 ! 3 ! 1 ! ( 1 + x 2 ) ( 8 x 3 ) ]  +  [ 1′
( 1 6 x 4 )
]

( 1 + x 2 ) 4  – 4  [ ( 1 + x 2 ) 3 ( 2 x ) ]  + 6  [ ( 1 + x 2 ) 2 ( 4 x 2 ) ]  – 4  [ ( 1 + x 2 ) ( 8 x 3 ) ]  +  ( 1 6 x 4 )  ----- (1)

Now,

( 1 + x 2 ) 4

= 4C0(1)4 + 4C1 (1)3 ( x 2 ) + 4C2(1)2 ( x 2 ) 2 + 4C3(1) ( x 2 ) 3 + C4 ( x 2 ) 4

( 4 ! 0 ! ( 4 0 ) ! 1 )  +  ( 4 ! 1 ! ( 4 1 ) ! 1′
x 2
)
 +  ( 4 ! 2 ! ( 4 2 ) ! 1′
x 2 4
)
 +  ( 4 ! 3 ! ( 4 3 ) ! 1′
x 3 8
)
 +  ( 4 ! 4 ! ( 4 4 ) ! 1′
x 4 1 6
)

= 1 +  ( 4′
3 !
1′
3 !
x 2
)
 +  ( 4′
3′
2 !
2′
1′
2 !
x 2 4
)
 +  ( 4′
3 !
3 ! 1 !
x 3 8
)
 +  ( 1′
x 4 1 6
)

= 1 + 2x +  3 x 2 2  +  x 3 2  +  x 4 1 6  ------------------- (2)

( 1 + x 2 ) 3

= 3C0(1)3 + 3C1 (1)2 ( x 2 ) +3C2 (1)  ( x 2 ) 2 + 3C3 ( x 2 ) 3

( 3 ! 0 ! ( 3 0 ) ! 1 )  +  ( 3 ! 1 ! ( 3 1 ) ! 1′
x 2
)
 +  ( 3 ! 2 ! ( 3 2 ) ! 1′
x 2 4
)
 +  ( 3 ! 3 ! ( 3 3 ) ! 1′
x 3 8
)

= 1 +  ( 3′
2 !
1′
2 !
x 2
)
 +  ( 3′
2 !
2 ! 1 !
x 2 4
)
 +  ( 1′
x 3 8
)

= 1 +  3 x 2  +  3 x 2 4  +  x 3 8  ------------------------ (3)

And,  ( 1 + x 2 ) 2

= 2C0(1)2 + 2C1 (1) ( x 2 ) + 2C2   ( x 2 ) 2

( 2 ! 0 ! ( 2 0 ) ! 1 )  +  ( 2 ! 1 ! ( 2 1 ) ! 1′
x 2
)
 +  ( 2 ! 2 ! ( 2 2 ) ! x 2 4 )

= 1 +  ( 2′  
1
1′
1 !
1′
x 2
)
 +  x 2 4

= 1 + x +  x 2 4  ---------------------------- (4)

Putting (2), (3) and (4) in (1) we get,

( 1 +   x 2 2 x ) 4

= 1 + 2x +  3 x 2 2  +  x 3 2  +  x 4 1 6  – 4  [ ( 1 + 3 x 2 + 3 x 2 2 + x 3 2 ) ( 2 x ) ]  + 6  [ ( 1 + x + x 2 4 ) ( 4 x 2 ) ]  – 4  [ ( 1 + x 2 ) ( 8 x 3 ) ]  +  ( 1 6 x 4 )

= 1 + 2x +  3 x 2 2  +  x 3 2  +  x 4 1 6  –  8 x – 12 – 6x –x2 2 4 x 2  +  2 4 x  + 6 –  3 2 x 3  –  1 6 x 2  +  1 6 x 4

1 6 x  +  8 x 2  –  3 2 x 3  +  1 6 x 4  – 4x+  x 2 2  +  x 3 2  +  x 4 1 6  – 5

 

Q10. Find the expansion of (3x2– 2ax + 3a2)3using binomial theorem.

A.10.  [ 3 x 2 2 a x + 3 a 2 ] 3

[ 3 x 2 + a ( 2 x + 3 a ) ] 3

We know that by binomial theorem,

( a + b ) 3  =  a 3 + b 3 + 3 a b ( a + b )

a 3 + b 3 + 3 a 2 b + 3 a b 2

Then,

[ 3 x 2 + a ( 2 x + 3 a ) ] 3

= (3x2)3 + [ a ( 2 x + 3 a ) ] 3  +  [ 3 ( 3 x 2 ) 2   a ( 2 x + 3 a ) ]  +  [   3 ( 3 x 2 ) { a ( 2 x + 3 a ) } 2 ]

= 27x6 + [ a 3 ( 2 x + 3 a ) 3 ]  +  [ 3 ( 9 x 4 ) ( 2 a x + 3 a 2 ) ]  +  [ 3 ( 3 x 2 ) { a 2 ( 3 a 2 x ) 2 } ]

= 27x6 + [ a 3 { 8 x 3 + 2 7 a 3 + 3 ( 4 x 2 ) ( 3 a ) + 3 ( 2 x ) ( 9 a 2 ) } ]  +  [ 5 4 a x 5 + 8 1 a 2 x 4 ]  + [  ( 9 a 2 x 2 )   ( 9 a 2 + 4 x 2 1 2 a x )  ]

= 27x6 + [ 8 a 3 x 3 + 2 7 a 6 + 3 6 a 4 x 2 5 4 a 5 x  ] + [  5 4 a x 5 + 8 1 a 2 x 4  ] + [  ( 8 1 a 4 x 2 + 3 6 a 2 x 4 1 0 8 a 3 x 3  ]

= 27x6   8 a 3 x 3 + 2 7 a 6 + 3 6 a 4 x 2 5 4 a 5 x     5 4 a x 5 + 8 1 a 2 x 4  +  8 1 a 4 x 2 + 3 6 a 2 x 4 1 0 8 a 3 x 3

= 27x6– 54ax5 +   1 1 7 a 2 x 4     1 1 6 a 3 x 3  +  1 1 7 a 4 x 2     5 4 a 5 x   +   2 7 a 6

Explore exams which ask questions on Maths Ncert Solutions class 11th

Select your preferred stream

qna

Maths Ncert Solutions class 11th Exam

Student Forum

chatAnything you would want to ask experts?
Write here...